2012
DOI: 10.1063/1.4735469
|View full text |Cite
|
Sign up to set email alerts
|

The transient behavior of Peltier junctions pulsed with supercooling

Abstract: There exists the transient thermoelectric supercooling effect that can be enhanced by keeping on increasing the Peltier cooling effect to compensate for the Joule heating effect and Fourier heat conduction effect arriving at the cold junction, in which a transient cold spike can be produced by superimposing an additional shaped current pulse of a large magnitude on the original steady-state optimum value. Most previous work on the transient supercooling mainly focused on the minimum supercooling temperature ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…It has been shown that by applying a quadratic pulse form, the supercooling effect can be improved over other forms [7]. Some other pulse forms present additional advantages [8], [9]. Here we explore the influence of the electric pulse shape in the supercooling effect when the dimensions of the thermoelectric device goes to the submicrometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that by applying a quadratic pulse form, the supercooling effect can be improved over other forms [7]. Some other pulse forms present additional advantages [8], [9]. Here we explore the influence of the electric pulse shape in the supercooling effect when the dimensions of the thermoelectric device goes to the submicrometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Such transient modes are constantly attract the attention of researchers [5,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] because such modes have advantages over the stationary steady state. For example, at certain times in a pulsed cooling mode [24][25][26][27][28][29] deeper cooling can be reached.…”
Section: Introductionmentioning
confidence: 99%
“…Higher current passed through the TE device for a short time delivers additional cooling. Optimization of length and shape of the current pulses can give deeper cooling on limited time intervals [27] or the cooling of small objects in a shorter time [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Variables that affect pulsed Peltier cooling include: thermoelement length, 15 current pulse amplitude 15,19 pulse duration, 19 pulse shape, 14,16,19,[22][23][24][25][26][27] time between pulses, 28 thermoelectric figure of merit, 15 thermoelement thermal diffusivity 15 , thermoelement shape [29][30][31] and the number of stages of a multi-stage thermoelectric cooler. 32 Of these variables, there are only two that can be varied to change the operating conditions for any given pulse shape.…”
mentioning
confidence: 99%